GENOTOXICITY OF CERIUM OXIDE NANOPARTICLE IN ZEBRAFISH AND GREEN MUSSEL PERNA VIRIDIS USING ALKALINE COMET ASSAY - Bhagat, Jacky; S G, S; Shyama, S K (LIFE: International Journal of Health and Life-Sciences, 2019)
Cerium oxide nanoparticles or nanoceria has versatile application in biomedical, solar cells and gas sensors. Increasing utilization of nanoceria has raised concerns over its release to environment and potential exposure. In vitro studies have shown its genotoxic potential, but reports on aquatic life are very limited. In this study, zebrafish (Danio rerio) and green mussel (Perna viridis) was exposed to different concentration 10, 20, 50 µg/l of nanoceria for 24, 72, and 120 h and the genotoxic response was measured using comet assay. The results showed significant (p < 0.05) increase in tail DNA (TDNA) and olive tail moment (OTM) as measured using comet assay in exposed animals as compared to control. The highest TDNA and OTM were measured after 120 h of exposure with 50 µg/l of nanoceria in zebrafish as well as in green mussel. The results of this study demonstrate that short-term exposure to nanoceria causes a genotoxic response in zebrafish and green mussel, hence its environmental release should be carefully monitored.